ANALISIS RISIKO KESEHATAN DAN KESELAMATAN KERJA (K3) PADA PROSES PEMASANGAN JARINGAN INTERNET FTTH (FIBER TO THE HOME) DENGAN METODE HIRARC (HAZARD IDENTIFICATION, RISK ASSESSMENT, AND RISK CONTROL) STUDI KASUS DI PT. JINDE GRUP INDONESIA - Mohammad Lathoiful Minan; Mohammad Jufriyanto; Hidayat Hidayat (LPPM Politeknik LP3I Medan, 2022)
The industrial sector is one of the fastest growing sectors today. This means that many workers are absorbed in the industrial sector, both the manufacturing industry and the service industry. The workers acts as a driving force for the company to achieve its goals. Every process that goes through to achieve company goals cannot be separated from the risk of work accidents. This study aims to determine the potential risks of K3 through hazard identification, risk assessment, and proposed risk control so as to reduce or minimize work accidents. The research was conducted at PT. Jinde Group Indonesia especially in installation of a new fiber to the home (FTTH) internet network division. PT. Jinde Group Indonesia is a company engaged in internet service providers (ISP) that prioritizes quality and customer satisfaction, especially in the Gresik-East Java area. The method used in this research is HIRARC (Hazard Identification, Risk Assessment, and Risk Control). The results showed that there were 7 work activities with 9 potential hazards, that are falling from the ceiling of the house, being scratched by a cutter, punctured by fiber optics, falling from stairs when tidying fiber cable installations and alternating ties, electrocuted when tidying fiber cable installations and alternating ties, exposed to splintered bricks, and crushed by the foot of the stairs. The results of the risk assessment show that 44,44% of the potential hazards are in the moderate category, 22.22% of low risk, and 33.33% of high risk. The proposed risk controls are engineering control, Personal Protective Equipment (PPE), and administrative control. Keywords : Occupational Health and Safety, HIRARC Method, Internet Network Company